Formal education for youth and adults deprived of liberty (Research, Society and Development, 2022)
The educational practice in the penitentiary system arises from the need for new opportunities and the resocialization of people deprived of liberty, since education has an emancipatory character and allows individuals to understand the concept of man and the society in which they are incorporated. In this context, this article aims to highlight the importance of schooling for individuals deprived of their liberty, to know the laws that regulate education for these individuals, to problematize the issue of school dropout and also to reflect on the construction of significant educational practices. It is a qualitative, documentary, and bibliographic study theoretically supported by authors who deal with contemporary social organization and, in this context, with schooling. In terms of prison education, the function of education is to teach the inmates and give them a different vision of the world, in order to find new forms of reintegration into society. Thus, with this bibliographic review, it could be stated that this educational system is not commented because there are not many research sources. Therefore, it is necessary to look for new researches on this topic in order to improve the teaching and allow the change of the incarcerated people.